Three-Dimensional Hybrid Code for Earth's Magnetotail Dymamics - De Bartolo, Rosita; Zimbardo, Gaetano; Greco, Antonella (My University, 2012)
This work is dedicated to the development and exploitation of a new threedimensional (3D) particle code for equilibrium plasma con gurations. The code is of the so-called hybrid type, that is ions are treated as particles and electrons as uid. The development of the code involved the use of techniques such as ion tracing, semi-Lagrangian methods, quadratic interpolation on a 3D grid, and 3D fast Fourier transforms. An iterative procedure was developed to asses the convergence of the required solution. The code has been applied to the study of the equilibrium structure of the Earth's magnetotail current sheet. Investigating such a structure has become a major scienti c challange since the unambiguos detection, by the Cluster spacecraft, of bifurcated current sheets. We have obtained a relatively wide class of solutions for the current sheet structure, and we found that the double peak current pro le is due to electrons when the ions are injected into an Harris-like quasineutral sheet, computing ion moments on a 3D grid in space, and the electron uid equations are solved with appropriate boundary conditions. A detailed comparison of the simulation results with in situ spacecraft observations is carried out, too, showing that our solutions are consistent with the experimental data.
Keywords: Magnetismo terrestre